2021
DOI: 10.2147/opth.s309703
|View full text |Cite
|
Sign up to set email alerts
|

OCT Variability Prevents Their Use as Robust Biomarkers in Multiple Sclerosis

Abstract: Objective: To evaluate the agreement between the peripapillary retinal nerve fiber layer (pRNFL) and foveal thickness (FT) measurements among three different spectral domainoptical coherence tomography (SD-OCT) instruments in a sample of multiple sclerosis (MS) patients and a healthy age-matched control group. Methods: An observational cross-sectional study with three groups: healthy subjects and MS patients w/w a previous clinical diagnosis of optic neuritis (ON) was conducted. The pRNFL and FT were measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…While some studies have shown a thinning in pRNFL thickness in MS patients without a history of optic neuritis ( Albrecht et al, 2012 , Gonzalez-Lopez et al, 2014 , Para-Prieto et al, 2021 , Parisi et al, 1999 , Syc et al, 2012 ), others have not found a significant difference between MS patients and controls ( Behbehani et al, 2016 , Knier et al, 2016 , Oberwahrenbrock et al, 2013 ). Most of these studies have adjusted for the age when comparing the pRNFL measurements between MS and controls.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…While some studies have shown a thinning in pRNFL thickness in MS patients without a history of optic neuritis ( Albrecht et al, 2012 , Gonzalez-Lopez et al, 2014 , Para-Prieto et al, 2021 , Parisi et al, 1999 , Syc et al, 2012 ), others have not found a significant difference between MS patients and controls ( Behbehani et al, 2016 , Knier et al, 2016 , Oberwahrenbrock et al, 2013 ). Most of these studies have adjusted for the age when comparing the pRNFL measurements between MS and controls.…”
Section: Discussionmentioning
confidence: 95%
“…Significant thinning of mGCIPL in non-optic neuritis eyes of MS patients is now firmly established ( Petzold et al, 2017 ). However, previous MS studies showed pRNFL thickness diagnostic sensitivity to be significantly variable, especially when considering non-optic neuritis eyes ( Albrecht et al, 2012 , Behbehani et al, 2016 , Gonzalez-Lopez et al, 2014 , Knier et al, 2016 , Oberwahrenbrock et al, 2013 , Para-Prieto et al, 2021 , Parisi et al, 1999 , Syc et al, 2012 ). A previous study reported the capacity of pRNFL thickness in assessing MS was lower as compared to mGCIPL ( Gonzalez-Lopez et al, 2014 ).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation